Cross-Slot Antenna with U-Shaped Tuning Stub for Ultra-Wideband Applications - Dawood Seyed Javan; Mohammad Ali Salari; Omid Hashemi Ghoochani (International Journal of Antennas and Propagation)
A novel design of an ultra-wideband (UWB) slot antenna is presented. This antenna operates as a transmitter and receiver antenna. Effects of the antenna dimensional parameters are studied through experimental and simulation results. Design procedures are developed and verified for different frequency bands. The experimental and simulation results exhibit good impedance bandwidth, radiation pattern, and relatively constant gain over the entire band of frequency. Antenna gain and directivity at boresight and in their maximum states are close to each other and indicate high radiation efficiency. To use the antenna as a linearly polarized antenna, the radiation pattern in E-plane is better than that in H-plane.